Enhancing students’ environmental literacy through STEM and project-based learning - Akylbekova Turar; Bebolat Ibashev; Salih Çepni; Zhazira Mukataeva; Klara Sarsekova; Ibraimov Aibat (Institute of Advanced Engineering and Science, 2026)
Amid escalating global environmental challenges and the increasing emphasis on sustainable development, enhancing students’ environmental literacy has become a critical priority in higher education. However, conventional instructional approaches remain predominantly theory-oriented and insufficient in fostering interdisciplinary thinking and real-world problem-solving competencies. Addressing this gap, this study proposes the integration of the science, technology, engineering, and mathematics–project-based learning (STEM–PjBL) model, which combines STEM education with PjBL to promote active engagement in authentic environmental problem-solving contexts. This study offers a novel contribution by implementing the STEM–PjBL approach within a Chemical Ecology course, thereby linking interdisciplinary STEM integration with the development of environmental literacy and systems thinking. A quantitative research design was employed involving 70 master’s students from Abai Kazakh National Pedagogical University with prior exposure to environmental disciplines. A 15-item diagnostic instrument was developed to assess environmental literacy, with content validity confirmed using Aiken’s V (0.70–0.91). Data were analyzed using descriptive statistics, correlation analysis, and Student’s t-test. The findings indicate a high level of environmental literacy (mean=85.1) and provide empirical evidence supporting the effectiveness of the STEM–PjBL approach. The results demonstrate improvements in systems thinking and environmentally responsible behavior, highlighting its potential to enhance environmental education practices in higher education.